Obecność socjologii/socjologow edukacji i młodzieży na XV Ogólnopolskim Zjeździe Socjologicznym = Presence of sociology/sociologists of education and youth at 15th Polish Congress of Sociology - Borowicz, Ryszard (1945-2014) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
From the perspective of a participant of many Congresses and a sociologist of education the author assesses the state of contemporary sociology of education as the renaissance of this sociological subfield. He explains it mainly as a result of the great breakthrough and first years of political transformation. Earlier, according to the author, young generation and education were derivative and minor issues which were unworthy of much attention.
Keywords: ponowoczesność; edukacja; młodzież; postmodernity; education; youth